Comparative Genomics Reveals Key Gain-of-Function Events in Foxp3 during Regulatory T Cell Evolution - Andersen, Kristian G.; Nissen, Jesper K.; Betz, Alexander G. (Frontiers in Immunology, 2012)
The immune system has the ability to suppress undesirable responses, such as those against commensal bacteria, food and paternal antigens in placenta pregnancy. The lineage-specific transcription factor Foxp3 orchestrates the development and function of regulatory T cells underlying this immunological tolerance. Despite the crucial role of Foxp3 in supporting immune homeostasis, little is known about its origin, evolution and species conservation. We explore these questions using comparative genomics, structural modeling and functional analyses. Our data reveal that key gain-of-function events occurred during the evolution of Foxp3 in higher vertebrates. We identify key conserved residues in its forkhead domain and show a detailed analysis of the N-terminal region of Foxp3, which is only conserved in mammals. These components are under purifying selection, and our mutational analyses demonstrate that they are essential for Foxp3 function. Our study points to critical functional adaptations in immune tolerance among higher vertebrates, and suggests that Foxp3-mediated transcriptional mechanisms emerged during mammalian evolution as a step-wise gain of functional domains that enabled Foxp3 to interact with a multitude of interaction partners.